Bridging cognitive reserve and cerebellar networks: counteracting brain damage in patients with Alzheimer’s disease at different clinical stages - Serra, Laura; Rizzuti, Martina; Bonarota, Sabrina; Caruso, Giulia; Di Domenico, Carlotta; Mancini, Matteo; Giove, Federico; Caltagirone, Carlo; Gelfo, Francesca; Petrosini, Laura (Frontiers in Cellular Neuroscience, 2026)
IntroductionAlzheimer’s disease (AD) is a progressive neurodegenerative condition characterized by cognitive decline and brain atrophy. Recent evidence shows that the cerebellum also undergoes structural and functional alterations. The concept of cognitive reserve (CR) explains individual resilience to brain pathology, while the hypothesis of cerebellar cognitive reserve (CbCR) sustains an enhanced activity in cerebellar networks at rest and a more efficient recruitment of accessory areas during cognitive tasks. This study investigated structural connectivity changes in cerebellar-cortical networks across the AD continuum.MethodsA total of 179 participants were enrolled, encompassing 46 AD patients, 51 with amnestic mild cognitive impairment (aMCI), 46 with subjective cognitive decline (SCD), and 36 healthy subjects (HS). CR was defined by years of formal education. Whole-brain T1-weighted images were analysed using source-based morphometry (SBM) to identify patterns of grey matter concentration (GMC) covariance.ResultsThree main networks were identified: the cerebellum-basal ganglia-cingulum (CBGC), the anterior cerebellum-supplementary motor arearetrosplenial cortex (ACSMARC), and the posterior cerebellum-orbitofrontal cortex (PCOC), with the cerebellum as the only common structure. All networks showed progressive reductions in GMC covariance along the clinical continuum, with a specific pattern of GMC reduction according to diagnostic groups. Importantly, CbCR modulated connectivity within all networks, with higher levels associated with preserved structural integrity and better cognitive outcomes.DiscussionThese findings provide evidence of progressive cerebellar-cortical disconnection in AD pathology and highlight cerebellar reserve as a potential protective factor, suggesting that the CbCR assessment and specific interventions tailored to the cerebellar cognitive functions may help delay the cognitive decline.